Industrial training report: ISHAK BIN ISMAIL - Ishak, Muhammad Faiz (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This report summarizes my internship experience at ISHAK BIN ISMAIL, where I gained practical exposure to marketing operations and business administration. During the five-month internship, I assisted in various marketing functions, including market research, digital marketing, customer relationship management, and promotional campaign execution. Key responsibilities included conducting competitor analysis, managing social media content, supporting sales strategies, and analyzing consumer behaviour trends. I also participated in business development initiatives, enhancing my skills in strategic planning and communication. Through this internship, I developed a deeper understanding of real-world marketing challenges and applied theoretical knowledge from my academic studies. The experience improved my analytical, teamwork, and problem-solving abilities while providing valuable industry insights. Overall, the internship at ISHAK BIN ISMAIL was a rewarding opportunity that strengthened my professional competencies and prepared me for a future career in marketing.